Development of service performance index for exclusive motorcycle lanes in Malaysia - Faez, Seyed Farzin (2011)
Evaluation of a particular facility in management and operation of land transportation system is very important. Measures of performance are quite complex and used in a wide variety of designing, planning and policy analysis of transportation systems and new explicit performance measures of transportation system. Currently, there are many studies available on evaluating the service performance of transportation amenities such as bicycle lanes, highways or even pedestrian walkways. However, there is a lack of information on assessing the service performance related to motorcycle lanes. Hence, this research intends to develop the service performance index model for exclusive motorcycle lanes. One of the important measures of performance in analyses of transportation facilities is Level-Of-Service (LOS). Level-of-service measures also characterize a set of all other measures of performance essential for transportation analysis and replicate mainly the attributes of the system that shape the user perception of the quality of service. The present dissertation describes the development of a methodology to determine service performance index under ideal conditions based on user perceptions of road performance metrics such as motorcycles speed, motorcycles volume, pavement quality, total lane width. At the same time, a comprehensive model has been developed, which presents the service performance model including level-of-service for exclusive motorcycle lane. Also all data were collected in three sites (Federal Highway F02, Putra Jaya Highway and Subang Jaya). Two hundred fourteen motorcycle riders contributed in a survey and rated the performance of 500-metre segment of exclusive motorcycle lane as filmed on videotapes depicting scenes from the rider‟s perspective. First, ten video clips were presented to 47 participants. Then, participants were asked for their opinion regarding the factors affecting the road performance after watching video clips (pre test). In another test (test two) participants were asked to rate (using predefined scores) the performance or service quality of clips on six-point scale ranging from excellent to very poor after watching video clips. Totally fifty video clips were captured illustrating motorcycle ride along the existing exclusive motorcycle lanes in Malaysia. In addition, backgrounds of the survey participants were also asked and collected. The results revealed four factors as the significant to road performance: motorcycle volume, surface pavement quality, traffic speed and the total lane width. Also the following parameters mention by participants but they are not significant important on road performance: signboard, lighting, shelter, drainage, maintenance road, pavement marking, available sight distance, access frequency point, horizontal and vertical curve and rest station. The data of these surveys were analyzed using ordered linear regression and logistic regression model to predict the performance level rating of exclusive motorcycle lanes. The linear regression and logistic regression results were then compared to each other and also compared to the scores of surveys collected from questionnaires. These two models have good correlation to each other. Result shows Logistic regression was a better predictor of the observations compare to linear regression (0.76 vs 0.75). The outcome provides guideline for engineers and transportation planners to evaluate different design options by changing the independent variables to find the best combination of factors to achieve the desired road performance. Also existing roadways can be evaluated to determine the present motorcycle performance level or level-of-service on all segments. On the other hand, this study is also seen as filling the existing knowledge gap between the various types of land transportation amenities and facilities such as pedestrians, bicycles, and vehicles which provides the state service performance index or level-of-service (LOS) of motorcycle facilities.